Hospital Universitario y biomérico San Juan de Dios de Girón (2017)
For the Santander capital it was proposed the development of a renovation plan from the general view that the main consolidation of the territory from the current systems, generating new dynamics that allow to satisfy the deficiencies and also to generate greater development and competitiveness, for which the suburban area of the municipality was chosen of Girón; the proposal consists of two corridors, known as the services and integrating corridor, which group related activities and seek stabilize dynamics that saturate the metropolitan area, opting for new factors spatial, formal, spaces for walking and staying.